A Fast and Reliable Method to Isolate Human Placental Macrophages. (24th May 2019) - Mezouar, Soraya; Ben Amara, Amira; Chartier, Céline; Gorvel, Laurent; Mege, Jean‐Louis
Abstract: Macrophages are specialized cells involved in recognition, uptake, and destruction of microorganisms. Human placental macrophages are poorly investigated because of the lack of a convenient protocol for their isolation. Here, we present a straightforward and reliable method to isolate macrophages from full‐term human placentas. After enzymatic digestion of placental tissue and centrifugation of the cell suspension on a Ficoll cushion, placental macrophages are selected using magnetic beads coated with anti‐CD14 antibodies. Isolated cells are characterized by flow cytometry. Ninety eight percent of isolated CD14 + placental macrophages also express the macrophage marker CD68. Thus, this efficient and reliable method yields placental macrophages at high purity and sufficient quantity for functional studies. © 2019 by John Wiley & Sons, Inc.